Causes and Consequences of the Dysregulated Maternal Renin-Angiotensin System in Preeclampsia - Lumbers, Eugenie R.; Delforce, Sarah J.; Arthurs, Anya L.; Pringle, Kirsty G. (Frontiers in Endocrinology, 2019)
A healthy pregnancy outcome depends on the activation of the renin-angiotensin-aldosterone system (RAAS) as a regulated, integrated response to the growing demands of the conceptus. Both the circulating RAAS and the intrarenal renin-angiotensin system (iRAS) play major roles in cardiovascular function and fluid and electrolyte homeostasis. The circulating RAAS becomes dysfunctional in preeclampsia and we propose that dysregulation of the iRAS plays a role in development of the clinical syndrome known as preeclampsia. Experimental studies in animals have shown that placental renin, when released into the maternal circulation, can cause hypertension. We postulate that abnormal placental development is associated with over-secretion of renin and other RAS proteins/angiotensin (Ang) peptides by the placenta/decidua into the maternal circulation. We hypothesise that this is because of increased shedding of exosomes and other placental particles into the maternal circulation that not only contain RAS proteins and peptides but also microRNAs (miRNAs) that target RAS mRNAs, and Ang II type 1 receptor autoantibodies (AT1R-AAs), that are agonists for, and have the same actions as, Ang II. As a result, there is both suppression of the circulating RAAS that is responsible for maintaining maternal homeostasis and activation of the iRAS. Together with altered vascular reactivity to Ang peptides, the iRAS causes hypertension, renal damage and secondary changes in the neurohumoral control of the maternal circulation and fluid and electrolyte balance, which contribute to the pathophysiology of preeclampsia.